CD26 inhibition enhances perfusion recovery in ApoE-/-Mice - Haverslag, René T.; Groot, Daphne de; Grundmann, Sebastian; Meder, Benjamin; Goumans, Marie-José; Pasterkamp, Gerard; Hoefer, Imo E.; Kleijn, Dominique P. de (Current vascular pharmacology, 2013)
Objective: The adaptive growth of blood vessels is important to prevent tissue loss following arterial occlusion. - Extravasation of monocytes is essential f...